Pengembangan Tes Elektronik Animasi pada Mata Pelajaran Biologi Kelas XI di SMAN 2 Mandau Kabupaten Bengkalis - Reza Safira Putri (Universitas Ivet, 2021)
In the implementation of the learning evaluation process, several potential errors can slow down and reduce the effectiveness and efficiency in viewing student learning outcomes. This is because the learning evaluation process when the COVID-19 pandemic at SMAN 2 Mandau was still semi-computerized and the teacher was forced to comb through the student exam files one by one after being sent back by the students so that it prolongs the evaluation process, then because the system applied is still semi-offline, it makes it easy students in cheating during the evaluation process. This study aims to create an online computerized system to replace the current system to facilitate students and teachers in carrying out the learning evaluation process. This research was conducted using the R&D (Research and Development) or ADDIE (analyze, design, develop, implementation and evaluation) version of the research by Luther-Sutopo. This animation-based electronic test then went through a product test with a validity test with an average of 0.83, a practicality test of 0.87, and an effectiveness test of 0.69. Keywords: Test, Animation, Evaluation, Learning, R&D.